Management of Type II Endoleak From Internal Iliac Artery Immediately After Endovascular Aneurysm Repair. (January 2017) - Hsu, Ming-Yi; Su, Ta-Wei; Su, I-Hao; Ko, Po-Jen; Chu, Sung-Yu
Inadvertent coverage of origin of internal iliac artery (IIA) during endovascular aneurysm repair may lead to type II endoleak. Except for open surgery, the endovascular solution is limited. We report a case with such complication that was successfully treated with coil embolization using retrograde extrastent approach. This is a new technique that has not been reported before, and as such, had been useful in the treatment of type II endoleak from IIA as an alternative to open ligation of IIA origin.